(untitled) (Academia Science Repository, 2023)
Anthropogenic factors are expressed in the conscious and unconscious direct or indirect influence of people on nature. The role and importance of ecoethics in solving the problems of anthropogenic climate change is highlighted in the article, and the relevance of ecoethics as a means of solving problems related to negative trends in human development and maintaining the stability of society’s development is analyzed.